1992
DOI: 10.1128/mcb.12.2.767
|View full text |Cite
|
Sign up to set email alerts
|

Linked spontaneous CG----TA mutations at CpG sites in the gene for protein kinase regulatory subunit.

Abstract: are thought to result from hydrolytic deamination of 5-methylcytosine residues in these sites. The gene for regulatory subunit of murine cyclic AMP-dependent protein kinase has two closely linked CpG sites, one of which is a strong hotspot for spontaneous CG-+TA mutations leading to cyclic AMP resistance in S49 mouse lymphoma cells. About 5% of mutants with a spontaneous mutation at this CpG site had also acquired a second CG-oTA mutation at the nearby CpG site. The two mutations were always at first positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Active processes of C → T transitional mutagenesis have been reported for fungi (Selker et al, 1993) and mammals (Steinberg and Gorman, 1992), which may be mediated by chromosome pairing or through cytosine methylation. In Neurospora, Centola and Carbon (1994) examined the centromere-specific repetitive DNA sequences and considered that the high sequence divergence, high AT content (65%), and predominantly transitional differences between sequences suggested operation of the repeat-induced point mutation (RIP) system (Selker et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Active processes of C → T transitional mutagenesis have been reported for fungi (Selker et al, 1993) and mammals (Steinberg and Gorman, 1992), which may be mediated by chromosome pairing or through cytosine methylation. In Neurospora, Centola and Carbon (1994) examined the centromere-specific repetitive DNA sequences and considered that the high sequence divergence, high AT content (65%), and predominantly transitional differences between sequences suggested operation of the repeat-induced point mutation (RIP) system (Selker et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids, Bacteria, and Expression of Kinase Subunits-Full-length nonfusion constructs for bacterial expression of murine C␣ and RI␣ subunits were made in the T7 promoter-containing vector pET-8c (or, for the R subunit plasmid, a variant lacking an EcoRI restriction site) as described previously (20,21). Glu-200, Ile-210, Ser-210, Thr-210, and Asp-324 mutations were introduced into the wild-type R subunit plasmid by cassette replacement using polymerase chain reaction-amplified cDNAs from S49 cell mutants (19).…”
Section: Methodsmentioning
confidence: 99%
“…Our study showed that C to T transitions were particularly common p53 mutations in spontaneous mammary carcinomas. One mechanism for the formation of these mutations is deamination of 5-methylcytosine (Steinberg and Gorman, 1992). The prevalence of this mutation may be related to the presence of a number of methylated CpG sites within the p53 gene.…”
Section: Discussionmentioning
confidence: 99%